Tapegrass, Eelgrass, or Wild Celery (Vallisneria americana Michaux): A Native Aquatic and Wetland Plant - Mohsen Tootoonchi; Lyn A. Gettys; Jehangir H. Bhadha (EDIS)
This 5-page document describes the main features of tapegrass and summarizes important habitat requirements for its growth and restoration. Written by Mohsen Tootoonchi, Lyn A. Gettys, and Jehangir H. Bhadha, and published by the UF/IFAS Agronomy Department, September 2019. http://edis.ifas.ufl.edu/ag437